2018
DOI: 10.1021/acs.jafc.8b01115
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about the Chemistry of Strawberry Aroma?

Abstract: The strawberry, with its unique aroma, is one of the most popular fruits worldwide. The demand for specific knowledge of metabolism in strawberries is increasing. This knowledge is applicable for genetic studies, plant breeding, resistance research, nutritional science, and the processing industry. The molecular basis of strawberry aroma has been studied for more than 80 years. Thus far, hundreds of volatile organic compounds (VOC) have been identified. The qualitative composition of the strawberry volatilome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 45 publications
9
57
0
1
Order By: Relevance
“…Later, it was demonstrated that under ABA stimulation the ABAR promotes ripening in strawberry fruit [19,48,95], through ABA binding [96]. The downregulation of FaABAR expression inhibits ripening, without rescued by addition of exogenous ABA, suggesting a crucial role for the ABAR receptor in strawberry ripening [46]. Regarding the FaABAR interaction with other potential signaling proteins, a leucine-rich repeat receptor-like kinase LRR-RLK gene, named as FaRIPK1 (for red-initial protein kinase 1), has been localized in the nucleus and plasma membrane, and its binding to FaABAR regulates strawberry fruit ripening [94].…”
Section: Abscisic Acid (Aba)mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was demonstrated that under ABA stimulation the ABAR promotes ripening in strawberry fruit [19,48,95], through ABA binding [96]. The downregulation of FaABAR expression inhibits ripening, without rescued by addition of exogenous ABA, suggesting a crucial role for the ABAR receptor in strawberry ripening [46]. Regarding the FaABAR interaction with other potential signaling proteins, a leucine-rich repeat receptor-like kinase LRR-RLK gene, named as FaRIPK1 (for red-initial protein kinase 1), has been localized in the nucleus and plasma membrane, and its binding to FaABAR regulates strawberry fruit ripening [94].…”
Section: Abscisic Acid (Aba)mentioning
confidence: 99%
“…Also, flavour can be determined by the presence of molecules such as anthocyanins and tannins, that grant slight and pleasing astringency [28]. Aroma, one of the most valued attributes of raspberry [44] and strawberry [45,46] fruits, is a parameter that depends on a number of factors such as concentration, combination, and the perception threshold of different volatile compounds [45][46][47], and the main aroma components include lipid-derived compounds, phenolic derivatives, amino acid-derived compounds, and mono-and sesquiterpenes [47].…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry aroma is mainly due to the complex blend of volatile organic compounds (known as volatilome—Bicchi and Maffei, 2012 ; Ulrich et al, 2018 ), which also contribute to the fruit flavor (Forney et al, 2000 ; Forney, 2001 ; Prat et al, 2014 ; Schwieterman et al, 2014 ). Although these molecules have a big impact on fruit sensorial qualities, they are found in very low concentrations (ranging between about 0.001 and 0.01% of fruit fresh weight) (Buttery, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, STR seems to be a difficult odor to define because no molecule is simply described with an STR. Strawberry is a very widespread fruit worldwide, but its odor is one the most complex natural odors, and thus it is difficult to clearly describe [42]. The case of Et-iB, which is the STR component in the target mixture, is an interesting example.…”
Section: Discussionmentioning
confidence: 99%
“…The strawberry furanone is another case of such an ambiguity. This monocyclic molecule is considered to substantially influence the odor of strawberry fruit [42]. However, the aroma description is complex and has stronger caramellic and cooked odors than it does fresh fruit odors ("fruity, caramelized pineapple-strawberry odor & taste; roasted" [33]; "intense caramellic, fruity, jam like odor with some resemblance to the odor of maltol; also reminiscent of cooked pineapple" [44]).…”
Section: Discussionmentioning
confidence: 99%